Hak Para Pihak dalam Penyelesaian Sengketa Sertifikat Hak Atas Tanah Tumpang Tindih sebagai Upaya Perlindungan Hukum - Cangtika Laurensia; Gunawan Djajaputra (Syntax Literate, 2023)
Currently, there are still many overlapping land title certificates. Many court decisions attempt to guarantee legal certainty. However, one court decision is certainly not enough to accommodate all the rights owned by both parties in a land dispute, considering that in civil decisions related to land, someone wins or someone loses or the lawsuit is only partially granted, or the lawsuit cannot be accepted. So in efforts to resolve a land dispute, there are various options for legal resolution of the case, namely checking the validity of the two certificates to the National Land Agency (BPN), administrative resolution of National Land Agency’s responsibilities to the Administrative Court, civil action, or criminal action to District Court, as well as efforts to resolve disputes between the parties to the District Court from the first level to judicial review. This research aims to gain an understanding of what rights the parties have in resolving overlapping land title certificate disputes. The research method used is normative legal research, the results of the research show that there is still a lack of role and responsibility for BPN in resolving disputes.